Deskripsi Motivasi Belajar Bahasa Arab Siswa Pengguna Media Pembelajaran Pop-Up Book - Nur Fakhrunnisaa; Rahmawati (P3I Luwu Raya, 2023)
The objective of this study was to elucidate the underlying factors driving the inclination to acquire proficiency in the Arabic language among students in the science stream of grade X at SMAN 7 East Luwu. The research in question falls under the category of descriptive research, employing a quantitative methodology. The study's sample consisted of students in the Xth grade science 2 class at SMAN 7 East Luwu. The sample methodology employed in this investigation was a complete or entire sampling approach. The utilised research tool was a questionnaire designed to assess the motivation levels of students in learning the Arabic language. The data collected in this research falls under the category of quantitative data. The employed methodology for data analysis is quantitative analysis, specifically utilising descriptive statistics. The findings of this study indicated that the drive to acquire proficiency in the Arabic language among grade X Science 2 students at SMAN 7 East Luwu was quite high, with an average range of 35% to 64% across several indicators of learning motivation.